PENEGAKAN HUKUM TINDAK PIDANA PROSTITUSI ANAK SECARA ONLINE BERDASARKAN SISTEM HUKUM INDONESIA - Robi Assadul Bahri (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2023)
The practice of child prostitution has caused various negative impacts, one of which is damaging the morale of the nation's next generation, so that it can threaten the survival of the nation and state in the future. Ironically, cases of child prostitution have soared by more than 50 percent since the Covid-19 pandemic hit Indonesia. This, of course, is of concern to the government and law enforcement officials, including the author as an academic. This research is legal research with a typology of normative legal research or doctrinal research that aims to produce arguments, theories or new concepts in solving the problems to be studied. The results of the study concluded that the arrangements for eradicating criminal acts of online child prostitution in Indonesia are scattered in several statutory provisions. Legal System Theory concluded that online child prostitution law enforcement in Indonesia is still considered not to be effective and optimal, so that in the future there is a need for system changes in online child prostitution law enforcement.